Introducing Autodesk Maya 2012 - Derakhshani, Dariush (Autodesk official training guide., 2011)
"Introducing Autodesk Maya 2012 is the ideal primer to getting started with Maya. Learn the Maya interface and the basics of modeling, rigging, animating, texturing, lighting, rendering, visualization, and visual effects. The expository text is reinforced with fun and challenging step-by-step tutorials, including creating a solar system, an alien hand, a steam locomotive, a toy wagon, and other projects that help you learn the ins and outs of this complex software. Professional visual effects artist and instructor Dariush Derakhshani leads readers through the nuances of the complex software without over-explaining or over-simplifying. The tutorials offer realistic, professional challenges for those new to 3D, and to those coming from another 3D application. Introducing Autodesk Maya 2012 is the perfect guide to get you up and running in the world's most popular professional 3D software application"--